THE PRAGMATIC ANALYSIS OF DIRECTIVE SPEECH ACT TYPES IN THE MAIN CHARACTER’S UTTERANCES IN THE MOVIE “FREE GUY” - Agustinus Alwin Tango; Arie Ananda Putra; Rahmat Djihar; Ambalegin Ambalegin (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This study applied a pragmatic study to obtain the types of directive speech acts in the movie